The adoption of digital culture as a mechanism for the survival of micro scale business industry among traders in east Malaysia: a literature review analysis - Halina Sendera Mohd Yakin; Sabariah Abd Rahim; Kamsilawati Kamlun; Nur Thara Atikah Zainal; Esther Jawing; Junaidah Januin (2022)
Digital culture has become part of world mainstream reality, and the phenomenon of Covid-19 pandemic has further boosted the importance of digital culture empowerment among the global community. Conventional businesses are affected by the pandemic due to the control of movement and physical encounters causing traders to switch to digital businesses. Due to the importance of digital world, especially in the endemic era, this study has been initiated to analyse the literature review on the adoption of digital culture in the micro scale business industries in East Malaysia. Content/text analysis of some of the scholars‟ scientific works and participant observations have been utilised for data collection. The study found that there was a lack of literature review on the adoption of digital culture as a mechanism for the sustainability or survival of micro scale business industry among traders in East Malaysia during the Covid-19 pandemic. It also found that there is a diversity in the corpus of knowledge, conceptual aspect as well as trends of the authors‟ and scholars‟ approaches. This study is important because 76.6% of the Micro, Small and Medium Enterprises (SMEs) is the micro scale businesses. SMEs makes up 99% of the 920,624 business establishments in Malaysia. Despite being the backbone of the business landscape in Malaysia, SMEs have performed poorly in the digitalisation aspect. It is hoped that this paper will be able to contribute significantly to the academicians and researchers who specialise in the epistemological thought or knowledge.